Phytosomes Loaded with Mastoparan-M Represent a Novel Strategy for Breast Cancer Treatment - Zhao H; Bao S; Chen S; Yang Q; Lou K; Gai Y; Lin J; Liu C; Liu H; Zhang C; Yang R (International Journal of Nanomedicine)
Hairong Zhao,1,2,* Shuangyan Bao,2,* Shuanglong Chen,1,* Qingmo Yang,1,* Kangliang Lou,3 Yating Gai,4 Jinyan Lin,5 Chaojie Liu,2 Heng Liu,2 Chenggui Zhang,2 Ruiqin Yang1 1Department of Breast Surgery, The First Affiliated Hospital of Xiamen University, School of Medicine, Xiamen University, Xiamen, People’s Republic of China; 2Yunnan Provincial Key Laboratory of Entomological Biopharmaceutical R&D, Dali University, Dali, People’s Republic of China; 3School of Medicine, Xiamen University, Xiamen, People’s Republic of China; 4Xiamen Research Institute of Food and Drug Quality Inspection, Xiamen, People’s Republic of China; 5School of Public Health, Xi’an Jiaotong University, Xi’an, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ruiqin Yang, Department of Breast Surgery, the First Affiliated Hospital of Xiamen University, School of Medicine, Xiamen University, Xiamen, People’s Republic of China, Email yrqxm0822@163.com Chenggui Zhang, Yunnan Provincial Key Laboratory of Entomological Biopharmaceutical R&D, Dali University, Dali, People’s Republic of China, Email chenggui_zcg@163.comPurpose: Mastoparan-M (Mast-M) has cytotoxic effects on various tumor cells in vitro, including liver cancer and colorectal cancer. However, the anti-tumor mechanism of Mast-M remains unclear and its potential for anti-tumor therapy has not been investigated. Herein, we aimed to develop a novel phytosome formulation loaded with Mast-M and evaluate its efficacy against breast cancer both in vitro and in vivo. Furthermore, we investigated the underlying anti-tumor mechanisms of Mast-M.Methods: The synthesis of Phy-Mast-M involved a co-solvent technique, followed by solvent evaporation. Its anti-tumor mechanism was investigated using CCK-8, clone formation, and apoptosis assays. Subsequently, the biodistribution and anti-tumor efficacy of Phy-Mast-M were assessed in vivo using the 4T1 tumor-bearing mouse model. Finally, the safety of Phy-Mast-M was evaluated in vivo.Results: The prepared Phy-Mast-M demonstrated an exceptional monodisperse size distribution (125.67 ± 45.79 nm), and exhibited excellent stability under different physiological conditions. Phy-Mast-M could inhibit 4T1 cells growth through multiple channels, including arresting cell growth cycle and disturbing mitochondrial membrane integrity. Phy-Mast-M proved significantly higher accumulation at tumor sites in a tumor-bearing mouse model as compared to free Mast-M. Moreover, in vivo anti-tumor studies demonstrated that Phy-Mast-M exhibited superior curative inhibitory effects on tumor growth and favorable biocompatibility.Conclusion: Phy-Mast-M demonstrates significant anti-tumor activity both in vitro and in vivo. Moreover, its potential for clinical translation suggests promising prospects for cancer therapy, offering more drug options for breast cancer patients. Keywords: breast cancer, Mast-M, phytosomes, cancer therapy, small molecule peptide